Corporate Leverage, Debt Maturity, and Credit Supply: The Role of Credit Default Swaps - Saretto, Alessio; Tookes, Heather E. (Review of Financial Studies, 2013)
[Does the ability of suppliers of corporate debt capital to hedge risk through credit default swap (CDS) contracts impact firms' capital structures? We find that firms with traded CDS contracts on their debt are able to maintain higher leverage ratios and longer debt maturities. This is especially true during periods in which credit constraints become binding, as would be expected if the ability to hedge helps alleviate frictions on the supply side of credit markets.]